1993
DOI: 10.1108/02686909310036269
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Auditor′s Relationship with the Audit Committee

Abstract: Gives examples of a number of organizations, committees, and commissions which have promoted both internal auditing and audit committees during the past two decades. Explores the need for a close working relationship between the internal auditor and the audit committee. Examines: (1) the evolution of both internal auditing and audit committees; (2) the Treadway Commission recommendations regarding the importance and role of audit committees and internal auditors; (3) ways in which internal auditors can work wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 1 publication
0
21
0
8
Order By: Relevance
“…Such relationships, when they are characterized by regular interactions and an open dialogue, are expected to aid the IAF's pursuit of effectiveness. Thus, IA effectiveness is expected to be influenced by its interactions with SM (Van Gansberghe, ; Mihret & Yismaw, ; Ahmad et al ., ; Cohen & Sayag, ), and with the supervisory board and the AC (Rezaee & Lander, ; Anderson, ; Barma, ).…”
Section: Four Building Blocks: Literature Review and Measurementmentioning
confidence: 99%
“…Such relationships, when they are characterized by regular interactions and an open dialogue, are expected to aid the IAF's pursuit of effectiveness. Thus, IA effectiveness is expected to be influenced by its interactions with SM (Van Gansberghe, ; Mihret & Yismaw, ; Ahmad et al ., ; Cohen & Sayag, ), and with the supervisory board and the AC (Rezaee & Lander, ; Anderson, ; Barma, ).…”
Section: Four Building Blocks: Literature Review and Measurementmentioning
confidence: 99%
“…En plus de la fonction d'audit interne, ces pivots comprennent la haute direction, le conseil d'administration, le comité d'audit et l'audit externe (Gramling et autres, 2004 ;Rezaee, 2005). Nous nous intéressons spécifiquement aux relations entre les auditeurs internes et les membres du comité d'audit, car il s'agit des principaux acteurs de la fonction d'audit interne (Davies, 2009 ;Gramling et autres, 2004 ;Mat Zain et Subramaniam, 2007 ;Rezaee, 2005 ;Rezaee et Lander, 1993 ;Roussy, à paraître ;Sarens, De Beelde et Everaert, 2009 ;Turley et Zaman, 2007).…”
Section: Les Relations Entre L'audit Interne Et Le Comité D'audit Et unclassified
“…In the 1970s, when audit committees performed only basic functions, it was suggested that they should meet four to six times annually—escalating to monthly meetings if they were to assume greater responsibility for receiving reports from internal auditors and becoming involved in an organization's public reporting, operations, policies and procedures (Perry, 1977). Others have suggested the relationship between audit committees and internal auditors must be ‘year‐round’ (Rezaee and Lander, 1993). Hence reports that contemporary audit committees of firms engaged in large and complex businesses are meeting only two or three times a year suggest that members are devoting little attention to the wide range of responsibilities they claim to be addressing.…”
Section: Role and Activities Of Audit Committees—in Practicementioning
confidence: 99%